The impact of traffic congestion on freight transport efficiency in a tourism corridor: A case study of the Denpasar–Gilimanuk road - Soimun, Ahmad; Sadri, Putu Diva Ariesthana; Navianti, Dynes Rizky; Fitri, Siti Nurlita (Journal of Applied Sciences in Travel and Hospitality, 2025)
Traffic congestion has a significant impact on the efficiency of freight transportation in tourism-intensive areas such as Bali. This study analyzes the impact of congestion on the Denpasar-Gilimanuk corridor by measuring travel delays, vehicle operating costs, and increased costs due to congestion. The mixed methodology combines quantitative analysis based on the Indonesian Road Capacity Guidelines (PKJI), Vehicle Operating Cost calculation with PCI, with qualitative interviews with 25 logistics stakeholders over 6 days, in conjunction with traffic surveys. The results show that during peak hours, the volume to capacity (V/C) ratio exceeds 1.02 with freight vehicle speeds dropping below 15 km/h. The regression analysis revealed a strong inverse relationship between traffic volume and vehicle speed, resulting in increasing operating costs. Congestion costs reached IDR 2,699/km for pick-ups and IDR 30,879/km for large trucks, a 60% increase over smooth traffic conditions. Interviews confirmed that delivery delays negatively impact supply chain reliability, particularly affecting the fulfillment of tourism needs. The research quantified the tourism logistics conflict in Bali, revealing that the overlap of peak tourist hours with delivery schedules increased waiting times by 56%. Recommendations include infrastructure improvements, dedicated freight lanes, implementation of smart traffic management, and scheduling of off-peak deliveries. The findings contribute to strategic transportation planning for multifunctional corridors serving both tourism and logistics sectors. Limitations of the study include the focus on national roads only and the short duration of data collection, which may not fully capture seasonal traffic variations. Future research should extend the observation period and include secondary road networks to better understand regional freight transportation dynamics.